Nuclear and Chloroplast Sequences Resolve the Enigmatic Origin of the Concord Grape - Wen, Jun; Herron, Sterling A.; Yang, Xue; Liu, Bin-Bin; Zuo, Yun-Juan; Harris, AJ; Kalburgi, Yash; Johnson, Gabriel; Zimmer, Elizabeth A. (Frontiers in Plant Science, 2020)
Despite the Concord grape’s commercial importance, its origin has remained unresolved for over 150 years without a comprehensive phylogenetic analysis. In this study we aimed to reconstruct the evolutionary history of the Concord grape using sequence data from four nuclear markers (AT103, GAI1, phyA, and sqd1), six chloroplast markers (matK, psbA-trnH, petN-trnC, ycf1, trnL-F, and trnS-G), and the chloroplast genome. We sampled extensively the Vitis species native to eastern North America as well as representative species from Europe and Asia, including the commercially important Vitis vinifera (wine grape), a bisexual native European species, and its wild progenitor, Vitis vinifera subsp. sylvestris. We also sequenced the chloroplast genome of one accession of the Concord grape and analyzed the chloroplast genome data with the recently published Vitis plastome data set. Phylogenetic analyses of the chloroplast and nuclear data using maximum likelihood and Bayesian inference support the hybrid origin of the Concord grape. The results clearly pinpoint the wine grape Vitis vinifera as the maternal donor and the fox grape Vitis labrusca, common in eastern North America, as the paternal donor. Moreover, we infer that the breeding history of the Concord grape must have involved the backcrossing of the F1 hybrid with the paternal parent V. labrusca. This backcrossing also explains the higher morphological similarity of the Concord grape to V. labrusca. This study provides concrete genetic evidence for the hybrid origin of a widespread Vitis cultivar; this is promising for similar future studies focused on resolving ambiguous origins of major crops and future efforts to create successful hybrid fruit crops.